Uma proposta de ensino de matemática para a educação básica - Nespolo, Rodrigo Fernando (2014)
This paper presents a school proposal for that has as interest the students' motivation to learn Mathematics. Several bibliographies that propose Mathematical Modeling as an alternative teaching Mathematics, connecting school knowledge to everyday studen were surveyed. Following, we describe our proposal of teaching applied to a class of sixth grade of elementary school in which the contents of a circle and its elements, irrational numbers and operations with decimals, through the activity we call "Feast of Mathematics" were worked. In this proposal, we illustrate how these math concepts are present in everyday life and can be worked into a series that does not include in the grade’s curriculum such subjects, fleeing the linear aspect present in most curricula programs. The methodology used in the research was qualitative and the data were collected at weekly meetings of teaching Mathematics during the months of October and November in the academic year of 2013. From the developed work, there were noticed significant improvements in students' interest in learning Math, which provided, consequently, improvements in individual performance of each student and in the class as a whole. The main feature observed in the students during the application work with Mathematical Modeling was the motivation to learn new mathematical content awakened by a significant content and approached in a different way.